2014
DOI: 10.4103/0253-7176.140701
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Nursing Students' Attitudes towards Mental Illness: Implications for Specific Academic Education

Abstract: Background:Health care professions are not immune to social prejudices and surprisingly share the general public's attitude attributed to people with mental illness. Nursing students are future health manpower research related to nursing students attitudes toward mental illness is limited.Aim:The aim of this following study is to examine the undergraduate nursing students’ attitudes toward people with mental illness.Materials and Methods:Cross-sectional descriptive design was adopted for the present study. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 20 publications
3
29
2
Order By: Relevance
“…Regarding the attitudes of nursing students towards people with mental illnesses, the data are inconclusive. While Henderson et al (2007) and Tee and Uzar Ozcetin (2016) have clearly found negative attitudes, other studies reached more ambiguous conclusions (Poreddi et al 2014).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding the attitudes of nursing students towards people with mental illnesses, the data are inconclusive. While Henderson et al (2007) and Tee and Uzar Ozcetin (2016) have clearly found negative attitudes, other studies reached more ambiguous conclusions (Poreddi et al 2014).…”
Section: Introductionmentioning
confidence: 96%
“…() and Tee and Uzar Ozcetin () have clearly found negative attitudes, other studies reached more ambiguous conclusions (Poreddi et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…But the total score of the attitude towards psychiatric knowledge and teaching was not significantly changed (table 5). Table ( 6) showed that out of 8 items of the attitude towards psychiatric treatment and hospitals, only three of them showed slight improvement after studying the course which includes: Psychiatrist has very little to do to help their patients, The practice of psychotherapy basically is fraudulent since there is no strong evidence that it is effective and Psychiatric treatment has been more effective in the recent year while the total score of the attitude towards psychiatric treatment and hospitals was not significantly differed. There was slight improve in the average total attitude score of the students being 92.67±7.90 before studying the course and 95.34±8.32 after it, with no significant difference (table7).…”
Section: Results:-mentioning
confidence: 99%
“…This finding is consistent with previous researches revealing that nursing student's attitudes towards mental illness and psychiatric patients have been changed for better after the psychiatric course (10, 17, 18&19). Also, Poreddi et al (6) mentioned that nursing students have significant positive attitudes toward mental illness and they agreed that psychiatric ill patients can enjoy them personal and social life events such as marriage, working, having children or family. However this finding is inconsistent with research indicating that students attitudes toward mentally ill patients show no change after clinical contact (20) as suggested by Singh et al (21) changing attitudes involves a complex process, depending on many factors rather than patient contact alone.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation